The Role of Digital Transformation in Human Resources Flexibility: An Analytical Study at the Ministry of Communications - General Company for Telecommunications and Information Technology - Ghaleb Ghulam*, Ibtihal; Hassoon Al-Taie, Ali (Journal of Economics and Administrative Sciences, 2024)
Purpose: The current research seeks to embody its primary objectives in diagnosing the relationship between the research variables (digital transformation, human resources flexibility), as well as defining the role of each of them in the General Company for Communications and Informatics.Theoretical Framework: This study deals with the General Company for Communications and Informatics and presents the latest concepts that previous researchers have reached to contribute to its achievement and expand the company's awareness by adopting any of these models appropriate to its goals and future direction.Design/Methodology/Approach: The study analyzes administrative data within the Ministry (2023-2024), using the dimensions of digital transformation and human resources flexibility to determine - the relationships between the variables and the factors affecting them.Findings: The results highlight the direct impact of digital transformation on human resources flexibility, emphasizing the importance of identifying the strengths and weaknesses of digital transformation and human resources flexibility within the General Company for Communications and Informatics.Research Implications: The results emphasize the increasing importance of integrating current research variables into formulating regulatory policies to address environmental changes and align them with the needs and aspirations of current and future beneficiaries.Originality/Value: This study enhances awareness of the importance of combining digital transformation and human resources flexibility in one study and bridges the knowledge gap between them.